2010
DOI: 10.1002/smi.1359
|View full text |Cite
|
Sign up to set email alerts
|

Emotional labor in china: do perceived organizational support and gender moderate the process?

Abstract: This survey study of 2201 employees from a large mobile phone company investigated how perceived organizational support (POS) and gender moderate the impact of emotional labor strategies on employee strain. Emotional labor strategies were related to employee strain, including turnover intentions, job satisfaction, burnout, and mental well‐being in the expected directions. POS moderated these relationships such that POS was related to more positive outcomes for employees who engaged in deep acting but exacerbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 59 publications
5
56
3
1
Order By: Relevance
“…One of the significant theories that can explain the behavior in organization is Social exchange theory (SET) (Cropanzano & Mitchel, 2005). According to social exchange theory employees reciprocate to the beneficial actions which may include pay, access to the information and work conditions that can aid to job performance, respect or support (Blau, 1964).This perceived organizational support can lead the employee to reciprocate the organizational support through the devotion to the emotions that are organizationally expected (display rules) which may result in decrease of emotional labor (Nixon, Yang, Spector, and Zhang, 2011). So that it is hypothisized that: "The percieved organizational support will be the significant predictor of emotional labor" A severe increase in emotional labor in the new job market experienced by many nurses results increase in job stress, poor health condition, greater self-alienation and sudden depressive moods (Kovacs, Kovacs, & Hegedus, 2010).…”
Section: Rationalementioning
confidence: 99%
“…One of the significant theories that can explain the behavior in organization is Social exchange theory (SET) (Cropanzano & Mitchel, 2005). According to social exchange theory employees reciprocate to the beneficial actions which may include pay, access to the information and work conditions that can aid to job performance, respect or support (Blau, 1964).This perceived organizational support can lead the employee to reciprocate the organizational support through the devotion to the emotions that are organizationally expected (display rules) which may result in decrease of emotional labor (Nixon, Yang, Spector, and Zhang, 2011). So that it is hypothisized that: "The percieved organizational support will be the significant predictor of emotional labor" A severe increase in emotional labor in the new job market experienced by many nurses results increase in job stress, poor health condition, greater self-alienation and sudden depressive moods (Kovacs, Kovacs, & Hegedus, 2010).…”
Section: Rationalementioning
confidence: 99%
“…According to the JDCS model, occupational support could moderate the association between emotional labor and mental health among employees who have to do high-strain emotional labor. In fact, previous research has reported that perceived organizational support influences employees' performances during emotional labor and moderates the association of emotional labor with job satisfaction, performance, and emotional exhaustion [23][24][25][26]. Besides organizational support, a variety of stress factors at work, such as the demands of the job, organizational injustice, and discomfort in the occupational climate, may influence the consequences of emotional labor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the recently published Fifth European Working Conditions Survey, 59% of European workers report working at high speed and 37% report not being able to choose their method of work [2]. Notably, among psychosocial factors, organisational constraints (i.e., not having job-related information, having limited time and materials, or not having the necessary authority to be able to complete one’s tasks) have been shown to be strongly related to physical symptoms, such as backache, headache or sleep disturbances [3]. …”
Section: Introductionmentioning
confidence: 99%
“…As Hargrove and colleagues [14] noted, at least a dozen theoretical models of organizational stress do exist: this means that a variety of non-identical approaches also exist, therefore it is important to explicit to which research paper is best to make reference. However, as Nixon and colleagues noted [3], theoretical models aimed at explaining the work-related stress process contain a huge amount of similar variables and elements (e.g., [15-17]). The underlying process posits a stimulus–response process in which job stressors lead to psychological or physical strain, and behavioural reactions, while a central role is played by individual appraisal of stressors.…”
Section: Introductionmentioning
confidence: 99%